Language in Clickbait Strategies: A Structural Analysis of Political News Headlines on IDN Times During the Regional Election Week (Tamaddun, 2025)
The rapid growth of technology has changed information media, making internet news easily accessible and extensively consumed. To attract readers, numerous online news platforms adopt clickbait methods, typically designing headlines designed to generate curiosity or emotional responses. This study explores the language tactics utilised in clickbait headlines published by IDN Times during the 2024 Indonesian Regional Elections (Pilkada) week. Using a qualitative descriptive technique and content analysis, the study analyzes 25 headlines picked by purposive sampling. Zhang’s rhetorical framework, which categorizes rhetorical elements into Hyperbole, Insinuation, Puzzle, and Visual Rhetoric, serves as the basis for the analysis. The statistics suggest that Insinuation is the most often utilised rhetorical component (12 occasions), followed by Hyperbole and Puzzle (10 instances each), and Visual Rhetoric (9 instances). These rhetorical methods effectively engage readers and shape their perspectives, particularly in the setting of political news. While clickbait boosts reader engagement, it also raises questions about media credibility and ethical journalism practices, especially when headlines overstate or mislead. This study contributes to the understanding of how language promotes public interaction with online news and underscores the need of media literacy in interpreting digital information. Future study could expand the scope to include larger datasets, numerous news platforms, or longitudinal analysis to explore the shifting dynamics of clickbait in digital media.